Manufacturing completion of the first ITER vacuum vessel sector. (1st July 2022) - Kim, H.S.; Moon, H.K.; Park, C.K.; Jung, Y.J.; Ha, M.S.; Park, S.H.; Joo, Y.M.; Joo, J.K.; Kang, S.G.; Seo, Y.H.; Han, J.Y.; Lim, N.J.; et al.
Abstract: In April 2020, manufacturing of the ITER vacuum vessel (VV) first sector has been completed by the Korean domestic agency, manufacturing having started in February 2012. The ITER VV sector is the largest fusion VV structure in the world. Each step of the manufacturing was a challenge as a first-of-a-kind, and a French nuclear pressure vessel. The paper provides an overview of the major challenges which were overcome over the last 10 years.